Spanish Contributions to I.F.T.U. Appeals : inter-departmental correspondence - Carthy, A. E.
001-0193-001 TRADES UNION CONGRESS GENERAL COUNCIL. INTER - DEPARTMENTAL CORRESPONDENCE. From A.E. CARTHY Department INTERNATIONAL To Miss F. E. MacDONALD. Date....January 4, 1937. SUBJECT. SPANISH CONTRIBUTIONS TO I.F.T.U. APPEALS After consulting the "Activities of the I.F.T.U. 1933-1935", I find the Spanish Centre has taken the following action in those years with regard to I.F.T.U. appeals: Matteotti Fund 1933-1934 NIL International Solidarity Fund 1935 NIL Austrian Relief Action 1933-1934-1935 33,726.33 French francs Saar Propaganda Action 1933-1934-1935 NIL. AEC/301. 292/946/1/193